CHANGING WRINKLES TO SMILES WITH PALLIATIVE CARE FOR THE ELDERLY! - Mohapatra, S C; Mohapatra, Archisman (Indian Journal of Community Health, 2012)
Over the past years, the conscious and collaborative efforts of Peoples and Planners world-wide have shown a reduction in mortality and increase in the life expectancy at birth. Thus, the world will be over loaded with aged people one century ahead; on the other hand, we in India have cheated this particular group for last 65 years by not providing any special care package for them – the Elderly: presenting them the “geriatric care”! The then Director-General of the World Health Organization, Gro Harlem Brundtland in 1999 had said “Population ageing is, rst and foremost, a success story for public health policies as well as social and economic development”. Thus, the WHO has aptly chosen the theme “Ageing and health: Good health adds life to years” for 2012. The focus is how good health throughout life can help older men and women lead full and productive lives and be a resource for their families and communities.[1] It is predicted that within the next five years, the number of adults aged 65 years and over will outnumber children under the age of 5 and by 2050, all children under the age of 14. Between 2000 and 2050, the proportion of the world’s population over 60 years will double from about 11% to 22% with the most rapid and dramatic demographic changes being seen in low and middle income countries.[2]